Legal Protection of Auction Buyers of Mortgage Objects Canceled by Court at the State Property Service Office and Auctions - Yusuf, Adrian Hasfi; Gunarto, Gunarto (Jurnal Konstatering, 2022)
This study aims to: analyze the legal remedies of mortgaged object buyers at the State Property Service Office and Auctions that were canceled, To analyze the legal protection of mortgaged object auction buyers at the State Property and Auction Services Office which were canceled by the court, To analyze the mortgage objects in Office of the State Assets and Auction Service which was canceled by the court. Research Methods: The empirical juridical approach is that this research means that in analyzing the problem, it is done by combining legal materials (which are secondary data) with primary data obtained in the field, namely about "Legal Protection Of The Position Of Buyer Auction Objects Of Liability Canceled At The Court' s Decision In The Office Services Of State Property And Auction In The City Of Pekalonganâ€ This type of research is analytical descriptive, that is, this research is analytical descriptive, which describes the data obtained from observations, interviews, documents and field notes, then analyzed in the form of a thesis to describe the problem with the title chosen, namely Legal Protection Of Object Auction Buyer Position Liability Rights Canceled Court Decisions At The State Property Service Office And Auction In Pekalongan City. From the approach, this research uses an empirical juridical approach.